2016
DOI: 10.3758/s13414-016-1163-y
|View full text |Cite
|
Sign up to set email alerts
|

Developmental improvements in the resolution and capacity of visual working memory share a common source

Abstract: The nature of visual working memory (VWM) representations is currently a source of debate between characterizations as slot-like versus a flexibly-divided pool of resources. Recently, a dynamic neural field model has been proposed as an alternative account that focuses more on the processes by which VWM representations are formed, maintained, and used in service of behavior. This dynamic model has explained developmental increases in VWM capacity and resolution through strengthening excitatory and inhibitory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…Moreover, performance on tasks involving color is better than performance on tasks involving shapes, and performance with familiar colors is better than performance with less familiar colors (Simmering et al 2015). Lastly, children's estimation of remembered color features becomes more precise (Simmering and Miller 2016).…”
Section: Improvements In Vwm: Capacity and Featuresmentioning
confidence: 99%
“…Moreover, performance on tasks involving color is better than performance on tasks involving shapes, and performance with familiar colors is better than performance with less familiar colors (Simmering et al 2015). Lastly, children's estimation of remembered color features becomes more precise (Simmering and Miller 2016).…”
Section: Improvements In Vwm: Capacity and Featuresmentioning
confidence: 99%
“…Cowan et al (2011) also found that articulatory suppression introduced to prevent rehearsal did not change the developmental pattern for these visual arrays. Simmering and Miller (2016) account for capacity development through an increase in the precision of representations in working memory, in a dynamic field model in which there are excitations related to the representations of stimulus qualities and inhibitory interactions between similar representations. More precise representations with age would reduce the inhibitory interactions within a stimulus set, but it is difficult to see how this process can account for a developmental difference in the concurrent retention of two very different stimulus sets (e.g., in Experiment 2, a color array and an instrument-based but non-musical tone sequence), with greater interference between sets when they are both taskrelevant as compared to when one set is task-irrelevant.…”
Section: Development Of the Speed Of Processing?mentioning
confidence: 99%
“…Thus, strengthening excitatory and inhibitory connectivity, and the resulting increase in real-time stability, could provide a mechanistic explanation for the cognitive improvements posited by other theories (see Simmering, 2016, for further discussion). This potential overlap between theories highlights the value of computational implementations, which can test whether a single set of processes could encompass characteristics of multiple competing theories (i.e., changes in both capacity and resolution, Simmering & Miller, 2016; see Johnson et al, 2014, for further details in the context of the slots versus resources debate in VWM).…”
Section: Discussionmentioning
confidence: 99%